Resilience of Women with Dual Roles in Higher Education Institutions: A Comparative Study of Indonesian and Malaysian Female Muslim Lecturer - Maisyanah, Maisyanah; Asror, Moh (PALASTREN: Jurnal Studi Gender, 2024)
This paper aims to compare the resilience of Muslim women Lecturer with dual roles in Indonesia (INa) and Malaysia (IMa). There are five indicators used, namely Wagnild and Yong indicators which are derived into 25 sub-indicators. The interview instrument is broken down from the 25 sub-indicators. This research uses a phenomenological qualitative approach. Data were obtained by interview method, offline and online. There are six Muslim women  Lecturer who became informants, three from Indonesian universities, and  the rest from Malaysian universities.  The discussion is presented by displaying the results of data analysis from Atlas.ti in the form of WordCloude, making it easier for readers to see the comparison. The first indicator of Equanimity, in Indonesia positive thinking is more dominant, while in Malaysia reflection is more dominant. Second, Perseverance indicators, which emerged from the two countries were purpose and intention (INa), meaningfulness (IMa). Third, Self Resiliance INa is Self-Confident, and IMa is Spirit. Fourth, there are five categories whose portions are balanced, (INa) namely Helpful, Ability, Greatful, Insatiate, and Resilient. While the IMa that appears is the Meaningfulness category. Fifth, the Existential Aloneness Indicator INa consists of Indifferent and Intuitive, while IMa is Indifferent and Cheerful. The results show strategies that can be used to improve resilience, such as developing a positive mindset, finding meaning in work, and building self-confidence.